Telaah Kualitas Hidup Pasien Penyakit Kronik di Kalimantan Barat - Untari, Eka Kartika; Yuswar, Muhammad Akib; Rizkifani, Shoma (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: The long duration of chronic disease affecting the patient’s quality of life. Every disease including chronic disease has a different duration and prognosis. The instrument that being used in measuring the quality of life can be very important factor. Quality of life assessment has a benefit by evaluate the treatment of patients with chronic disease, moreover the good quality of life will also increase the patient's life expectancy. The purpose of this article are to describe and identify instruments that being used to measure quality of life patients with chronic disease in West Kalimantan.Methods: This study conduct to review the original research articles with the keywords "quality of life", "chronic disease", and "West Kalimantan". Twenty three research articles were obtained in Google Scholar and met the inclusion criteria. The generic instruments such as WHOQOL-BREF and EQ5D are the most widely used to measure the patient’s quality of life.Result: The distribution of chronic diseases that have been assessed were hypertension, chronic renal failure, diabetes mellitus, COPD, pulmonary tuberculosis, asthma, myocardial infarction, stroke, CHD, osteoarthritis, HIV / AIDS, and psoriasis. The disease with the most impact on quality of life is hypertension (6 of 23 articles). There were 53.07% patients has a good quality of life; 15.97% patients has a moderate quality of life; and 30.96% patients has a bad quality of life.Conclusion : Most of the hypertensive patients has a good quality of life compared to other disease groups. Health interventions were needed to improve the quality of life for patients with chronic diseases.